Ozone-biorregulatory medicine integrative therapy to regulate gonartrosis in octogenaries (Ozone Therapy Global Journal, 2018)
Gonarthrosis is a chronic, degenerative and progressive joint affection of the knee joint. It is the most frequent articular disease affecting mainly to obese population, women, and over 40 years old group of age. It is being able of producing disability of the patient.The aim of this study was to investigate the effects of OZONE-BIORREGULATORY MEDICINE treatment in the evolution of Gonarthrosis. The sample of the study consisted in 5 patients, 3 women and 2 men. In these patients, we meassured pain and variation in the ability for proper function of the join. Our testing hypothesis: OZONE-BIOREGULATORY MEDICINE will reduce pain, increase functionality and consequently will improve the quality of life of treated patients to a greater extent than previous treatments.Method: To verify the hypothesis, as an experimental condition, the following combined treatment has been used: treatment with intraarticular and systemic ozone, such as minor autohemotherapy, local bioregulatory medicine with Traumeel, Zeel, Lymphomiosot, Coenzyme compositum and Systemic with Galium heel, Thalamus compositum and Testis or Ovarium compositum and post-treatment test. Pain tests and proper functioning of the joint tests were performed before and after the treatment to measure the evolution of the patient. The pre-treatment tests have also used as experimental control. Significant results were obtained with a P